The Exact Controllability of the Molecular Graph Networks - Liang Wei; Faxu Li; Haixing Zhao; Bo Deng; Zhonglin Ye (Journal of Chemistry)
In this paper, we mainly study the exact controllability of several types of extended-path molecular graph networks. Based on the construction of extended-path molecular graph networks with C3, C4, or K4, using the determinant operation of the matrix and the recursive method, the exact characteristic polynomial of these networks is deduced. According to the definition of minimum driver node number ND, the exact controllability of these networks is obtained. Moreover, we give the minimum driver node sets of partial small networks.